Influence of the preparation method on the performance of Ni-based bifunctional catalysts in the one-pot conversion of γ-valerolactone to valeric biofuel - Martínez Figueredo, Karla Geraldine (2020)
In this work the one-pot production of pentyl valerate (PV) from γ-valerolactone (GVL) and pentanol in liquid phase at 523 K, 10 bar of H2 over Ni-based catalysts supported on SiO2-Al2O3 (SA) was studied. By using incipient wetness impregnation (I) and precipitation-deposition (PD) two different catalysts were prepared, characterized and tested in reaction. With larger Ni0 particles and a significantly higher acid site density, Ni/SA-I was more active and selective to PV, revealing the crucial impact of preparation method on the catalytic performance. After 24 h, a GVL conversion of 83.5% with PV selectivity of 87.8% was reached with Ni/SA-I.